2019
DOI: 10.1177/0276146719882746
|View full text |Cite
|
Sign up to set email alerts
|

Content is King: How SMEs Create Content for Social Media Marketing Under Limited Resources

Abstract: Despite the growing literature dealing with social media marketing (SMM) in small and medium-sized enterprises (SMEs), one area that has not been fully explored is the creation of the content itself. SMEs typically do not have the same resources available that larger companies possess. Therefore, they have to find alternative ways to compensate for this weakness. This study analyzes SMEs’ SMM content creation, specifically on Facebook. By first scanning existing literature for essential factors for content cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 54 publications
1
51
0
3
Order By: Relevance
“…PEU can be realized when SMEs believe that the involvement of a quality management system will help them promote achievement (Davis, 1989;Davis et al, 1989). Furthermore, when SMEs look at the benefit of using Social Media Marketing (SMM) to lead to better productivity, there is no doubt that they will adopt this method in their business (Kraus, Gast, Schleich, Jones, Ritter et al, 2019). Previous studies by Chatterjee and Kumar Kar (2020); Qalati et al (2021) found that utilizing SMM will promote the SMEs' performance.…”
Section: Perceived Of Usefulness (Peu)mentioning
confidence: 99%
“…PEU can be realized when SMEs believe that the involvement of a quality management system will help them promote achievement (Davis, 1989;Davis et al, 1989). Furthermore, when SMEs look at the benefit of using Social Media Marketing (SMM) to lead to better productivity, there is no doubt that they will adopt this method in their business (Kraus, Gast, Schleich, Jones, Ritter et al, 2019). Previous studies by Chatterjee and Kumar Kar (2020); Qalati et al (2021) found that utilizing SMM will promote the SMEs' performance.…”
Section: Perceived Of Usefulness (Peu)mentioning
confidence: 99%
“…Surprisingly, 30% of the e-retailers in our sample do not conduct any digital marketing tactics in foreign markets. For small e-retailers, it would be worthwhile to invest in skills and technical knowledge in using digital marketing tactics effectively (Lam and Harker, 2015; Taiminen and Karjaluoto, 2015), which will help establish processes and routines that can support the burden of limited resources (Kraus et al, 2019). When digital marketing tactics are used, it is important for small e-retailers to employ a combination of multiple digital marketing tactics in foreign markets.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, research and knowledge on small e-retailer strategies and the use of digital marketing tactics in foreign markets have tended to be based on insights from larger e-retailers (Colton et al, 2010). However, it is recognised that approaches to marketing for small firms differ from those of their larger counterparts (Bocconcelli et al, 2018; Jones and Rowley, 2011; Kraus et al, 2019). Small firms usually have fewer resources available for the execution of digital marketing tactics (Eggers et al, 2017; Mazzarol, 2015; Taiminen and Karjaluoto, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…La revisión de la literatura sobre la cuestión del uso de redes sociales en el ámbito de las estrategias de marketing, tanto en la empresa como en la universidad, deja un sin fin de referencias. En lo que atañe al uso de redes sociales en el contexto empresarial, los autores destacan los trabajos de: Alonso (2015), Matosas López (2018), Mukherjee y Banerjee (2019), Kraus et al (2019), o Giakoumaki y Krepapa (2019).…”
Section: Las Redes Sociales En El áMbito De Las Estrategias De Marketingunclassified
“…Los autores demuestran que la publicidad en esta red puede generar en la audiencia una actitud positiva hacia la marca, aumentando además la intención de compra de los productos o servicios de la compañía. Kraus et al (2019), por su parte, examinan, a través de entrevistas personales, los protocolos de creación de contenido seguidos por una muestra de PYMES (pequeñas y medianas empresas) en sus páginas de empresa en Facebook. Los autores concluyen que, a pesar de la limitación de recursos (tanto humanos como económicos), estas empresas son conscientes de los aspectos a considerar en la gestión de sus estrategias de marketing en este medio.…”
Section: Las Redes Sociales En El áMbito De Las Estrategias De Marketingunclassified